Kuka oli herra Heinäricki? - piispa Henrikin arvoitus - K. Heikkilä, Mikko (Tampere University Press, 2016)
The present multidisciplinary study deals with the legendary bishop Saint Henry of Finland ‒ both the historical person and his medieval ecclesiastical cult, as well as the vernacular folk tradition including The Death-lay of Bishop Henry. The book contains an English and Swedish summary.